The global dash for cash: Why sovereign bond market functioning varied across jurisdictions in March 2020 - Jordan Barone; Alain Chaboud; Adam Copeland; Cullen Kavoussi; Frank Keane; Seth Searls (Federal Reserve Bank of New York, 2022)
As the economic disruptions associated with the COVID-19 pandemic increased in March 2020, there was a global dash-for-cash by investors. This selling pressure occurred across advanced sovereign bond markets and caused a deterioration in market functioning, leading to central bank interventions. We show that these market disruptions occurred disproportionately in the U.S. Treasury market and were due to investors' selling pressures being far more pronounced and broad-based. Furthermore, we assess differences in key drivers of the market disruptions across sovereign bond markets, based on an analysis of the data as well as structured outreach to a range of market participants.
Keywords: G01; G12; E44; H63; 330; sovereign bond markets; financial crisis; COVID-19